Vulvar melanocytic nevus: case report - Mariana A. Almeida; Berenice A. Coelho (Sociedade Brasileira de Patologia Clínica, 2020)
ABSTRACT Pigmented vulvar lesions are uncommon; they occur in about 10%-12% of women and include benign and malignant processes, as well as post-inflammatory changes and hyperchromatic lesions due to melanin increase. Among the benign processes, there are vulvar nevi, present in 2% of adult women. There is a small subgroup classified as atypical melanocytic nevi that account for 5% of vulvar nevi and is associated with younger women. Despite the importance of early diagnosis, the clinical history and time of evolution of the lesion are not well explored, as patients rarely examine the region, as do dermatologists. We report a case of an melanocytic nevus in the small lip in a 43-year-old woman.